Lowering the sintering temperature of solid oxide fuel cell electrolytes by infiltration - Sindirac, Can; Cakirlar, Seda; Büyükaksoy, Aligül; Akkurt, Sedat (Elsevier Sci Ltd, 2019)
A dense electrolyte with a relative density of over 95% is vital to prevent gas leakage and thus the achievement of high open circuit voltage in solid oxide fuel cells (SOFCs). The densification process of ceria based electrolyte requires high temperatures heat treatment (i.e. 1400-1500 degrees C). Thus, the minimum co-sintering temperatures of the anode-electrode bilayers are fixed at these values, resulting in coarse anode microstructures and consequently poor performance. The main purpose of this study is to densify gadolinia doped ceria (GDC), a common SOFC electrolyte, at temperatures lower than 1400 degrees C. By this aim, an approach involving the infiltration of polymeric precursors into porous electrolyte scaffolds, a method commonly used for composite SOFC electrodes, is proposed. By infiltrating polymeric precursors of GDC into porous GDC scaffolds, a reduction in the sintering temperature by at least 200 degrees C is achieved with no additives that might affect the electrical properties. Energy dispersive x-ray spectroscopy line scan analyses performed on porous GDC scaffolds infiltrated by a marker solution (polymeric FeOx precursor in this case) reveals a homogeneous infiltrated phase distribution, demonstrating the effectiveness of polymeric precursors.
Keywords: SOFC; GDC; Electrolyte; Microstructure; Densification; Infiltration